2003
DOI: 10.1002/bip.10427
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight effects on the glass transition of gelatin/cosolute mixtures

Abstract: The structural properties of four gelatin fractions in mixture with sucrose and glucose syrup have been investigated extensively using small deformation dynamic oscillation. The total level of solids was 80%, the number average molecular weight of the protein ranged from 29.2 to 68 kD, and the temperatures were between 60 and -60 degrees C. Remarkably, the nature of the time and temperature dependence on the viscoelastic functions of all samples could be reduced to master curves using horizontal shift factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 67 publications
3
18
1
Order By: Relevance
“…The tendency of increment of viscosity and bloom strength within the same source of gelatin is in good agreement with literature (Kasapis, Al-Marhoobi, & Mitchell, 2003). However, these previous works did not use gelatins from different sources.…”
Section: The Buffering Effect Of Gelatinsupporting
confidence: 90%
“…The tendency of increment of viscosity and bloom strength within the same source of gelatin is in good agreement with literature (Kasapis, Al-Marhoobi, & Mitchell, 2003). However, these previous works did not use gelatins from different sources.…”
Section: The Buffering Effect Of Gelatinsupporting
confidence: 90%
“…Some gelling processes, particularly those involving fibrous proteins, are induced by the effect of heating followed by cooling, leading to the entanglement of chains, such as in gelatin [1]. The effect of other species, such as sugar, on gelation in these instances is relevant and has been extensively studied [2].…”
Section: Introductionmentioning
confidence: 99%
“…8 The good agreement between bulk gel and membrane elastic properties found here is slightly surprising as gelation is not an instantaneous process; it has been observed that stiffening of gels may continue to occur for more than 6 h after gelation temperature is reached 24 and that the stiffness of the gel is also dependent on its temperature. 12 As membranes are very thin structures, they will desiccate much faster than a bulk gel of the same cross-sectional area due to a high surface area-to-volume ratio. Significant water loss coupled with rapid cooling may interfere with proper coil to helix transitions and thus generation of a highly interlinked solid matrix.…”
Section: Discussionmentioning
confidence: 99%